Bee Pollen Effect on Blood Glucose Levels in Alloxan-induced Male Wistar Rats - Rahayu, Aprilia Nurcahyaning; Wirjatmadi, Bambang; Adriani, Merryana; M., Soenarnatalina; Winarni, Dwi; Hartiningsih, Sri (Health Notions, 2018)
a